Debt sustainability of state-owned enterprises in Indonesia - Esther Sri Astuti Soeyaningrum Agustin; Eko Listiyanto; Nur Komaria (Cogent Business & Management)
This study examines the debt sustainability of State-Owned Enterprises (SOEs) in Indonesia to evaluate its implications for the country’s fiscal health. The rising external debt of SOEs, which has surpassed private businesses in recent years, has raised significant concerns among stakeholders. Employing financial risk tools, this research compares the performance of SOEs relative to their peers and assesses their vulnerability through stress tests and government mitigation strategies. Key financial indicators, including profitability, liquidity, leverage, and efficiency, are analyzed for 16 SOEs listed on the Indonesian Stock Exchange from 2017 to 2021. The findings reveal considerable risks to SOE debt sustainability across industries, with no sector being consistently secure or unstable. However, SOEs in the mining sector demonstrate better debt sustainability performance than those in the construction sector. While some SOEs face significant risks in managing their debt, others remain positioned to meet their financial obligations. The study underscores the critical need for stakeholders to closely monitor and manage SOE debt, as it directly affects the fiscal performance of the Indonesian government.